2017
DOI: 10.18203/2319-2003.ijbcp20170332
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication prevalence and related factors among medical university students, 2015

Abstract: Background: Self-medication is one of the main health problems. Given the high prevalence of self-medicationin society and between students, the aim of this study was to assess the rate of self-medication among Ardabil medical students.Methods: This cross–sectional study has been done on 150 students which selected randomly from Ardabil Medical University Science students. Data collected by a questionnaire and then analyzed by statistical method in SPSS.19.Results: The rate of self-medication among students wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 5 publications
1
9
2
1
Order By: Relevance
“…However, our study revealed lower self-medication prevalence than some studies [22,35,36,37,12,13,17,18,15,38,39,40,41,36,42].…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…However, our study revealed lower self-medication prevalence than some studies [22,35,36,37,12,13,17,18,15,38,39,40,41,36,42].…”
Section: Discussioncontrasting
confidence: 92%
“…While other study from north India among nursing students was 88.24% [17], Brazil among nursing students 76.0% (18), and Kuwait among medical students was 97.8% [19]. On other systemic review from Ethiopia indicates self-medication varied from 12.8% to 77.1% [20],Iran university was 65% [15], Eastern Saudi Arabia indicates 90.5% [21], medical students in Coastal South India 78.6% [22], 86%…”
Section: Systemic Review Registrationmentioning
confidence: 99%
See 3 more Smart Citations